DIGITALIZATION AND ITS IMPACT ON SOCIETY - ŞAHİN, İrem Mihrab; MERMUTLU , M. Bedri (SSD Journal, 2022)
The development and advancement of machines and technology has changed the way of production. The changing production system has passed through certain stages and has become artificial intelligence technology, smart production, automation, sensors and digitalization, which is called Industry 4.0 today. Digitalization in the production system has covered every aspect of our daily lives and has affected daily practices and relationships. With digitalization, there have been changes and transformations in many areas such as institutions, factories, professions, education, finance, security, health. This change and transformation has also been reflected in social and individual life. This study is written on how digitalization affects the basic concepts that shape society such as production, division of labor, identity, privacy, socialization, time and space. With the spread of the Internet and social media, identities that define the individual and society have turned into virtual identities. Virtual identities, which are independent of physical time and space, have changed the way socialization is done. The new form of virtual socialization requires the user to be online at all times. The widespread use of social media has spawned new social movements, and these new social movements are using social media as a tool of political transformation. Virtual communities isolate the individual and alienate him from the society and culture in which he lives. The changing individual also affects the social structure and reveals the new society. Increasing internet use and digitalization have also increased surveillance and supervision. The traces we leave in the virtual world are converted into data with artificial intelligence technology and the individual is confronted with advertisements and products according to their interests. The storage of data calls into question the security and privacy of the individual and makes the concept of cyber security important. The changing and transforming concept of security affects the emergence of new crimes and the legal infrastructure to combat these crimes.